Comparison of Performance of Photodiodes with Different Active Areas Using Acrylic and Quartz Cuvettes for Spectrophotometry in Direct Measurements of Glucose in Water and Human Blood Plasma by Optical Means Using Near-Infrared - De La Cruz Cortes, Victor; Segura Félix, Kristian; Flores García, Francisco Gerardo; Cepeda Rubio, Mario Francisco Jesús (Journal of Spectroscopy, 2022)
Diabetes mellitus is one of the most relevant noncommunicable diseases; the WHO figures in its latest update that 422 million people suffer from it; additionally, it has remained for more than 20 years within the 10 main causes of death worldwide; this disease affects the population at any age; glucose measurement is used to assist the treatment of this disease by different methods that are classified as invasive, minimally invasive, and noninvasive, the latter being an area of recent development due that it is not traumatic for patients. This work consists of the experimental characterization of an optical system for plasma glucometry using near infrared by spectrophotometry. This glucometry system is based on the employ of an infrared LED with a wavelength of 1650 nm, a beam angle of 16°, and an output power of 1.6 mW that passes through the analyte (glucose in blood plasma) that is contained in cuvettes of different materials (acrylic and quartz) to subsequently affect a photodiode with different active areas ranging from 0.06 mm to 1.5 mm in order to evaluate the efficiency by comparing the sensitivity in the presence of glucose making additions ranging 100 mg/dl–1000 mg/dl within a dark chamber. The experiments showed that the use of photodiodes with a larger active area and the use of quartz cuvettes show a higher sensitivity compared to photodiodes with small active areas and the use of acrylic cuvettes. This configuration presented an R2 of 0.99 and a sensitivity of 0.225 mV/1 mg/dl of glucose; despite the fact that the initial voltage in each of the experimental repetitions varies, the downward voltage pattern is maintained; based on this, it is concluded that this method using this setup is feasible for plasma glucose measurement.